Inflammatory Response Against Staphylococcus aureus via Intracellular Sensing of Nucleic Acids in Keratinocytes - Ngo, Quang Vinh; Faass, Larissa; Sähr, Aline; Hildebrand, Dagmar; Eigenbrod, Tatjana; Heeg, Klaus; Nurjadi, Dennis (Frontiers in Immunology, 2022)
Staphylococcus aureus is one of the clinically most relevant pathogens causing infections. Humans are often exposed to S. aureus. In approximately one-third of the healthy population it can be found on the skin either for long or short periods as colonizing “commensals”, without inducing infections or an inflammatory immune response. While tolerating S. aureus seems to be limited to certain individuals and time periods in most cases, Staphylococcus epidermidis is tolerated permanently on the skin of almost all individuals without activating overwhelming skin inflammation. To investigate this, we co-cultured a keratinocyte cell line (HaCaT) with viable S. aureus or S. epidermidis to study the differences in the immune activation. S. aureus activated keratinocytes depicted by a profound IL-6 and IL-8 response, whereas S. epidermidis did not. Our data indicate that internalization of S. aureus and the subsequent intracellular sensing of bacterial nucleic acid may be essential for initiating inflammatory response in keratinocytes. Internalized dsRNA activates IL-6 and IL-8 release, but not TNF-alpha or IFNs by human keratinocytes. This is a non-specific effect of dsRNA, which can be induced using poly(I:C), as well as RNA from S. aureus and S. epidermidis. However, only S. aureus were able to induce this response as these bacteria and not S. epidermidis were actively internalized by HaCaT. The stimulatory effect of S. aureus seems to be independent of the TLR3, -7 and -8 pathways.